Web-Based Melviana Health Clinic Information System - Rendi Brahma Fahrezi (Journal of Business Social and Technology, 2020)
In today's globalization era, nscience and technology are developing very rapidly, especially information technology. Human need for everything is required to be more efficient, for example it is very clear from the development of information technology, the work that originally still uses a lot of manual systems at this time has begun to decrease, because it began to practice to a computerized system. Because with a computerized process any work will be easier to do. In the process of developing data and information needs that are growing longer, has encouraged better handling of data and information so that each element can be implemented optimally the author to get information relevant to the topic and problems that will or are being researched. The information can be obtained from scientific books, research reports, yearbooks and written sources both printed and electronic.